Effect of replacing sodium erythorbate and nitrate with three Nigerian indigenous spices on the quality and sensorial characteristics of frankfurter sausage (2023)
Sausage is a meat product that is prepared by combining different meat types that are commuted and seasoned with various spices and additives which include sodium erythorbate and nitrate. The main objective of this study was to evaluate the effect of replacing both sodium erythorbate and nitrate with three Nigerian indigenous speies, Parkia biglobosa, Piper gidneense and Monodora myristica, each of the spice constituted a treatment, while the control was a Frankfurter sausage with both sodium erythorbate and nitrate thus: T0 = FF (control) T, = PB, T2 = PG and T3 =MM each contained 10% of the spices. The sausages samples were analyzed for physical, chemical, minerals and vitamins, microbiological and sensorial properties in a completely randomized design experiment and the significant means separated at p<0.05. Treatment 3 furnished highest yield, protein, mineral and vitamins, fiber, lowest microbial load, but highest eating properties and acceptability. It might be expressed from this study that indigenous spices are potential substitutes for sodium erythorbate and nitrate salts in sausage manufacture. From this study, it can be concluded that Monodora myristica can be used effective to replace the two salts in sausage to guarantee the quality and acceptability of the final product by consumers.